The influence of research centers on American policy towards Africa: the international and political journal - Kazim, Prof. Dr. Muhannad Abdul Wahid; Hussein, Randa Alwan (The International and Political Journal, 2024)
This study aims to clarify the impact of American research centers on American policy towards African issues through studies, analyses, information gathering, and providing it to the American administration, which in turn saves the political decision-maker more time and effort. These centers work to put forward recommendations provided by their experts to find solutions to every issue related to the countries of the continent, in addition to the conferences, meetings and seminars that discuss them and achieve the initial step to control the countries of the continent. The United States of America’s interest in the countries of the African continent began in the eighth decade of the twentieth century to confront the Soviet competitor on the continent at that time. After the end of the Cold War, the African continent occupied an advanced position among American research centers, as was evident in the United States’ interest in the continent after several visits by American presidents such as Presidents Barack Obama and Joe Biden. These visits carried an indication of the United States’ interest in the continent and the recommendations of research centers to move towards a new strategy studied by it in confronting competing powers, especially China, Russia, India, Turkey, Iran and Israel, in addition to their clear influence in shaping American policy to confront the challenges facing the countries of the continent, whether on the economic or geopolitical level, which the United States of America follows and serves to achieve interests.